Pengawasan Badan Permusyawaratan Desa Dalam Penyelenggaraan Pemerintah Desa Di Desa Bojongkapol Kecamatan Bojonggambir Kabupaten Tasikmalaya - Asep Nurdin Rosihan Anwar; Ai Nurmalasari; Yogi Wijaya Dipura; Putri Pransiska Pasundan; Atep Ramdani; Irfan Erfiana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research describes the BPD's supervision of the implementation of village government in Bojongkapol village, Bojonggambir District, Tasikmalaya Regency, and is motivated by a lack of supervision regarding BPD supervision of the implementation of village government, a lack of Human Resources (BPD), and their understanding of their duties and functions. The methodology used in this research is a descriptive analysis method with a qualitative approach. The sources of information in this research were 5 (five) participants. The aim of this research is to find out how the Village Consultative Body (BPD) monitors the implementation of village government in Bojongkapol Village, Bojonggambir District, Tasikmalaya Regency. Research findings show that supervision by the Village Consultative Body (BPD) in administering the Bojongkapol Village Government is inadequate. The obstacles encountered were a lack of communication between the Village Consultative Body (BPD) and the Village Government, a lack of communication between BPDs and a lack of Human Resources (BPD) who understood their responsibilities and duties. Efforts made include establishing communication with the village government, distributing supervision schedules to each government department in the village, and conducting outreach regarding the responsibilities of the Consultative Body (BPD).